Antimicrobial effect of Phospholipid produced from Bacillus subtilis (World Journal of Experimental Biosciences, 2014)
Bacillus subtilis produces several antimicrobial compounds with different structures. These antimicrobial compounds showed antimicrobial effect against Gram positive and Gram negative bacteria. The present study aims to evaluate the antimicrobial effect of phospholipid produces from Alkaliphilic B. subtilis isolated from different samples of food against different species of bacteria (Gram positive, Gram negative and actinomycetes) and fungi, and study the effect of pH and temperature on the antimicrobial activity of phospholipid. The results showed that the phospholipid produced from B. subtilis inhibited the growth of Gram negative bacteria (Escherichia coli, Proteus mirabilis and Pseudomonas aeruginosa), Gram positive bacteria (Staphylococcus aureus and Enterococcus faecalis), Actinomyces sp. and fungi (Aspergillus niger, Candida albicans) with different inhibition zones. It was observed that the antimicrobial activity of phospholipid was decreased at high temperature (50 0C) and pH (10). It can be concluded that the phospholipids produced from B. subtilis has anti-microbial activity and that affected by incubation condition (temperature and pH).